Removal of ferrum (II) from industrial waste water by using dried water hyacinth Eichhornia Crassipes - Wahidah, Ab Rahman (2010)
Several contamination of industrial wastewater in Hunstman Tioxide (M) Sdn Bhd at Kemaman is Ferum (II). Ferrum (II) is non-biodegrable can be accumulated in living tissues, causing various diseases and disorders. The study is conducted to investigate the effects of biosorbent dosage, orbital shaker speed and contact time on the removal of Ferrum (II) from the industrial wastewater using non-living water hyacinth (Eichhornia Crassipes). The experiment was carried out for six weeks, where one week was spent for collecting water hyacinth (Eichhornia Crassipes) and preparing the biosorbent. The experiments for investigating the effects of biosorbent dosage, orbital shaker speed, and contact time were run during the different range. This study of the effect biosorbent dosage was run at the selected range (0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.1, 0.25, 0.20, 0.25, 0.30, 0.35, 0.40, 0.50, 0.55, 0.60, 0.65, 0.70, and 0.75 grams). Besides, the effect of orbital shaker speed experiment was done by shaking the samples at five different speed of orbital shaker (60, 90, 120, 150, and 175 rpm). Meanwhile, the effect of contact time was studied at the different contact time within three hours (0, 20, 40, 60, 80, 100, 120, 140, 160, and 180 minutes). All the samples were analyzed using the UV-Vis Spectrophotometer. From the result obtained, the optimum conditions for Ferrum (II) ions removal were at 0.75 g of biosorbent dosage, 175 rpm of orbital shaker speed and 180 minutes of contact time. As a conclusion, it is clearly shows that a biomaterial produced from dried water hyacinth can provide a simple, effective and yet cheaper method in removing Ferrum (II) from wastewater.